Corporate acquisition strategies and economic performance – A case of Slovenia - Vladimir Malenković; Matej Lahovnik (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2011)
The purpose of this paper is to examine the factors that influenced the performance of acquisitions in Slovenia. The empirical research methodology is based on qualitative part (interviews by using questionnaire) and quantitative part (descriptive statistics, correlation, regression model). In the methodology subjective approach (performance perceived by managers) is combined with more objective criteria. The performance of an acquisition is measured by comparing the acquisition’s motives with its outcomes. The acquisitions were divided into three types: horizontal, vertical and conglomerate. The result of this research implicates that the so-called strategic and organizational fit between companies involved in M&A play an important role in improving the operational performance of the acquired companies in the post-acquisition period. Successful acquirers not only had a background in detecting below-average or less than full potential performance, but they also had some skills and competencies to improve the performance of an acquired firm. The results of our study suggest the conclusion that increasing relatedness – especially with regard to certain competencies and skills – between companies involved in an acquisition increases the chances of success.